Construction and mechanical properties of boron carbide/regenerated cellulose composite fiber based on copper ammonia method - Yin Tang; Shouwei Ban; Jing Sun; Jianhua Zheng (PLoS ONE, 2026)
The fabrication and mechanical properties of boron carbide/regenerated cellulose composite fibers prepared via the copper ammonia method were investigated. The process involves dissolving cellulose in a copper ammonia solution, incorporating boron carbide powder, and subsequently performing wet spinning to produce composite fibers. The results indicate that the addition of boron carbide significantly alters the surface morphology and color of the fibers, rendering them rougher and darker. EDS analysis confirms the presence and distribution of boron carbide within the composite fibers, while TG analysis reveals enhanced thermal stability with increasing boron carbide content. XRD and FTIR analyses provide detailed insights into the crystal structure and functional groups of the composite fibers, confirming the successful incorporation of boron carbide into the cellulose matrix. Mechanical property evaluations show that smaller boron carbide particles (500 nm) have a more pronounced detrimental effect on the fracture strength of the composite fibers, likely due to agglomeration and the formation of stress concentrations. The post-treatment with glutaraldehyde at optimal concentrations and reaction times can enhance the tenacity of the composite fibers.